Pendampingan penyusunan laporan keuangan berdasarkan SAK EMKM pada UMKM di Desa Sukosari - Sugiharti, Rr. Retno; Khabibah, Nibras Anny; Septiani, Yustirania (Penamas: Journal of Community Service, 2024)
Recently, MSMEs have still experienced problems in accessing capital. This is mainly due to the lack of adequately recorded, structured, standardized financial reports. MSMEs still use simple records that do not refer to SAK ETAP. With the principle of convenience and expecting that MSMEs will be able to gain more comprehensive access to capital, SAK EMKM exists as a simpler financial reporting standard compared to the complicated SAK ETAP. Unfortunately, since it was established in 2018, MSMEs still rarely use financial reports based on SAK EMKM. Therefore, to socialize the use of SAK EMKM to MSMEs, it is necessary to provide inclusive assistance. With focussing in Sukosari Village, Magelang Regency, where the majority of the village population are running MSMEs, community service activities were carried out in the form of assistance to provide socialization and assistance regarding bookkeeping and prepare financial reports based on SAK EMKM. The evaluation results showed an increase in understanding of MSME actors in Sukosari Village regarding SAK EMKM by 65.45 percent, from recording manual financial reports to recording using simple SAK EMKM standards. The obstacles faced in implementing activities are a lack of understanding from business actors or managers regarding the correct flow of financial recording and the importance of financial reports.